Reference Value Evaluation of Urine Sediment in Indonesian Adult Population Using Automated Urine Analyzer - Eirene Jaquelene Tomatala; Anton Sumarpo; Hani Susanti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Locally established clinical laboratory reference value are required to interpret laboratory test results for screening, diagnosis, prognosis, determining retest criteria or as microscopic confirmation. The objective of this study is to establish urine sediments reference value by using automated urine flow cytometry, investigating erythrocyte, leukocyte, epithelial cells, types of epithelial cells, bacteria, casts, pathologic casts, crystals, yeast, sperm, and mucus in Indonesian population using Sysmex UF-4000. A cross sectional study was conducted in October 2018 – April 2019 at R. Said Sukanto National Police Hospital in Jakarta. The study involved 240 participants comprised of clinically healthy 120 males and 120 females aged 18-65, with normal urine chemistry, hematology, blood glucose, liver function (AST, ALT), and renal function (urea, creatinine). The reference value was reported in microliter (μL) or in High Performance Field (HPF) or Low Performance Field (LPF). Mann-Whitney test through MedCalc software was used to test significant differences with p value <0.05. This study observed significant differences between males and females in erythrocyte, epithelial cells, epithelial cell variety, bacteria, pathologic casts, and yeast—which are evidently higher in female patients. However, the mucus in LPF levels is found to be higher in male patients instead of the female, disparate than current reference value. Therefore, the reference value results were separated between the two groups in those aspects, whereas the results of other urine sediment characteristics studied were combined. As most reference value obtained are still within range of existing references, reference value established with Sysmex UF-4000 can be useful.